Mali : Technical Assistance Report-Anti-Corruption and Anti-Money Laundering. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key finding of the Technical Assistance Report on Anticorruption and Anti-money Laundering in Mali. The report suggests that the adoption and effective implementation of an Anti-Money Laundering/Combating the Financing of Terrorism (AML/CFT) framework compliant with the Financial Action Task Force (FATF) Recommendations would support the fight against corruption in Mali. Mali can improve the compliance of its AML/CFT framework with the FATF Recommendations by taking internal measures consistent with the West African Economic and Monetary Union directive. Mali can also work for the adoption of a regional AML/CFT framework consistent with the requirements of the FATF.